Effect of high contents of dietary animal-derived protein or carbohydrates on canine faecal microbiota - Hang, Ingrid (BioMed Central, 2012)
BACKGROUND: Considerable evidence suggests that food impacts both the gastro-intestinal (GI) function and the microbial ecology of the canine GI tract. The aim of this study was to evaluate the influence of high-carbohydrate (HC), high-protein (HP) and dry commercial (DC) diets on the canine colonic microbiota in Beagle dogs. Diets were allocated according to the Graeco-Latin square design. For this purpose, microbial DNA was isolated from faecal samples and separated by density gradient centrifugation, resulting in specific profiling based on the guanine-cytosine content (%G + C). In addition, 16 S rRNA gene amplicons were obtained from the most abundant %G + C peaks and analysed by sequence analysis, producing a total of 720 non-redundant sequences (240 sequences per diet). RESULTS: The DC diet sample showed high abundance of representatives of the orders Clostridiales, Lactobacillales, Coriobacteriales and Bacteroidales. Sequence diversity was highest for DC diet samples and included representatives of the orders Lactobacillales and Bacteroidales, which were not detected in samples from the HP and HC diets. These latter two diets also had reduced levels of representatives of the family Lachnospiraceae, specifically Clostridial cluster XIVa. The HC diet favoured representatives of the order Erysipelotrichales, more specifically the Clostridial cluster XVIII, while the HP diet favoured representatives of the order Fusobacteriales. CONCLUSIONS: This study detected Coriobacteriales in dog faeces, possibly due to the non-selective nature of the %G + C profiling method used in combination with sequencing. Moreover, our work demonstrates that the effect of diet on faecal microbiota can be explained based on the metabolic properties of the detected microbial taxa.